Effects of Opuntia ficus-indica flower extract WS 1261 on mental and psychic function in subsyndromal fatigue – A pilot study - Gaby Kressel; Janina Willers; Heike Kohrs; Andrea Zimmermann; Stephan Klement; Angelika Dienel; Andreas Hahn (International Journal of Phytomedicine, 2016)
Background Traditional use, chemical constituents, and results of prior animal studies indicate alleviating effects of Opuntia ficus-indica flowers extract on subsyndromal fatigue symptoms in humans Methods 50 healthy subjects of either gender aged 30 to 60 years with subsyndromal fatigue were enrolled in this open-label monocentric single arm proof-of-principle study. 500mg of a hydro-alcoholic extract from Opuntia ficus-indica flowers were administered daily over 8 weeks. Mental and psychic function parameters were assessed by numerical analogue scale of Subjective Fatigue Symptoms, Multidimensional Fatigue Inventory 20, Sheehan Disability Scale, Short Form Health Survey 36, Fatigue Impact Scale, and Global Self-Assessment. Also, health-related incidents, laboratory parameters and vital signs were measured during the intervention period. Results Improvement of fatigue symptoms could be shown in most measurements after week 1 and continued further throughout the trial. 70.0% of subjects reported global improvement of their complaints at end of study. Conclusions A consistent and positive effect of Opuntia ficus-indica flowers extract on symptoms of fatigue could be demonstrated. Improvement in all mental and psychic functions could be measured, most of them statistically significant.